Konstruiranje strojev in naprav: Učbenik - Kramberger , Janez; Pehan, Stanislav; Glodež, Srečko (2023)
This textbook provides a comprehensive introduction to modern systems procedures in the design of machines and devices. The main purpose of the textbook is first to provide simple guidance on how to meet the general requirements for the safety of machinery, set out in the relevant European and Slovenian legislation. Then, some guidelines for the ergonomic design of machinery are given. The main part of the textbook deals with the hazards and risk assessment associated with the mechanical design and use of machinery, and the complex subject of machine safety engineering is also described in detail. Finally, the basic environmental impacts of machinery are briefly described. The textbook is primarily intended for students of mechanical engineering in the course Design of Machines and Devices, but is also suitable for courses on related topics. The textbook contains a number of practical examples and is therefore also a useful aid for mechanical design engineers, who deal with the problems of machine design and safety in their daily practice.E-book available only for students of the University of Maribor, Faculty of Mechanical Engineering.
Keywords: design; machinery and devices; technical regulations and standards; working environment; ergonomics; hazards and risks; safety engineering